Tirbanibulin as a Novel Treatment in Actinic Keratosis: A Literature Review - Sajkiewicz, Ilona; Miga-Orczykowska, Nadia; Lemieszek, Paulina; Jasiuk, Ilona; Pustelniak, Martyna; Wójtowicz, Justyna; Krukar, Katarzyna; Rudnicka, Katarzyna; Łukaszewska, Ewa; Kister, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Actinic keratosis (AK) is a common dermatological condition that primarily affects fair-skinned individuals due to cumulative ultraviolet light exposure, potentially leading to squamous cell carcinoma (SCC). AK therapy is divided into two main branches: lesion-directed therapy (cryotherapy, lasers, and surgical methods) and field cancerization-directed therapy (photodynamic therapy and topical agents). Unfortunately, the occurrence of local skin reactions (LSRs) and the therapy duration counted in weeks disrupt patient compliance. This study aims to review the clinical trials concerning the efficacy, safety, and adverse effects of tirbanibulin, a novel promising treatment for AK, which led to its approval and therapeutic development. Materials and methods: Literature available in PubMed and GoogleScholar databases were reviewed using the following keywords: actinic keratosis; actinic keratosis treatment; tirbanibulin. Results: Tirbanibulin's mechanism involves inducing apoptosis by inhibiting microtubule polymerization, which distinguishes it from other treatments that often cause significant inflammation. Clinical trials demonstrate its high efficacy in clearing AK lesions with a favorable safety profile, leading to regulatory approval. The ease of use and short therapy duration (5 days) ensure patient compliance and satisfaction with the treatment. Conclusion: Further longitudinal studies are necessary to confirm the long-term benefits and positioning of tirbanibulin in AK therapy. Raising public awareness about AK and the importance of early treatment with effective options like tirbanibulin is crucial for improving public health outcomes.